Les abris sépulcraux de la presqu’île de Narinda (Province de Mahajanga, Madagascar) - Frédérique Valentin (OpenEdition, 2007)
This paper presents the preliminary results of an archaeological survey carried out in five funerary rock shelters in the karst (tsingy) of the Narinda region, on the North-West side of Madagascar. This project was conducted in the framework of a French-Malagasy co-operation for palaeontology and archaeology in the Mahajanga Province. The dead –men, women and children–, had been laid in wooden coffins with engraved lids which have the shape of canoes. The corpses had been definitely laid following strictly respected rules based on gender and cardinal points. Drawing on archaeological and ethnographic comparisons, the authors propose, in the first instance, a connection with burial traditions practiced by the Sakalava groups who settled the region during the 18th century.